2005
DOI: 10.2105/ajph.2004.049338
|View full text |Cite
|
Sign up to set email alerts
|

Injuries at Work in the US Adult Population: Contributions to the Total Injury Burden

Abstract: Injuries at work comprise a substantial part of the injury burden, accounting for nearly half of all injuries in some age groups. The NHIS provides an important source of population-based data with which to determine the work relatedness of injuries. Study estimates of days away from work after injury were 1.8 times higher than the Bureau of Labor Statistics (BLS) workplace-based estimates and 1.4 times as high as BLS estimates for private industry. The prominence of occupational injuries among injuries to wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
99
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 41 publications
7
99
0
5
Order By: Relevance
“…Studies have shown a tendency for college students to be less safety conscious from one decade to the next in terms of health and safety behaviors such as wearing a bicycle helmet and use of tobacco products 11,16) . This leads us to ask the question if longer tenure at the same job leads to a less safetyconscious worker, especially among university student employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown a tendency for college students to be less safety conscious from one decade to the next in terms of health and safety behaviors such as wearing a bicycle helmet and use of tobacco products 11,16) . This leads us to ask the question if longer tenure at the same job leads to a less safetyconscious worker, especially among university student employees.…”
Section: Discussionmentioning
confidence: 99%
“…Workers compensation records show that adults aged 20-24 yr had a significantly higher risk for injury than older adults [10][11][12] . Injury rates peak in young men aged 18-24 years, the age range of most employed university students 11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of all burn injuries in the US 4) . In addition to burn and cut injuries, low back pain (LBP) is prevalent in these working populations found in previous studies [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that burnout will increase the risk of all kinds of injuries, not just the ones occurring at work. This is worth studying, as injuries are common among working populations but less than one-third of injuries occur at work 21) . There are many possible mechanisms that may link burnout to all-cause injuries 18) .…”
mentioning
confidence: 99%